Morpho-anatomical responses of Sertani and Trisakti upland rice genotypes to contrasting soil moisture regimes - CHAIRANI HANUM; BRYAN DEVA SIMATUPANG (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Hanum C, Simatupang BD. 2026. Morpho-anatomical responses of Sertani and Trisakti upland rice genotypes to contrasting soil moisture regimes. Biodiversitas 27 (3): d270334. https://doi.org/10.13057/biodiv/d270334. Water availability critically determines upland rice agronomic performance, necessitating characterization of genotypic responses across moisture gradients. This study evaluated morpho-anatomical responses of two upland rice genotypes (Sertani and Trisakti) under contrasting moisture regimes of 40%, 60%, and 80% field capacity (FC) during the vegetative phase, using a factorial Randomized Complete Block Design (RCBD) with three replications. As FC increased from 40% to 80%, both genotypes showed significant (p<0.05) progressive increases in leaf area, leaf thickness, Relative Chlorophyll Index (RCI), bulliform cell dimensions, stomatal length, stomatal width, stomatal density, root volume, and total biomass. Root volume increased nearly five-fold from 0.25 cm³ at 40% FC to 1.23 cm³ at 80% FC, while total plant dry weight increased 3.9-fold (0.20 to 0.78 g) over the same gradient. Anatomical cross-sections revealed moisture-dependent structural differentiation: at 40% FC, plants displayed reduced cortical aerenchyma with endodermal lignification, whereas at 80% FC, extensive aerenchyma development was observed; these observations are qualitative and descriptive. Observed root:shoot ratios were numerically highest at 40% FC (Sertani: 0.50; Trisakti: 0.82); however, as these represent treatment means only and were not subjected to replicate-level statistical testing, no inferential conclusion regarding biomass allocation shifts is drawn. Trisakti showed numerically higher mean values than Sertani for root volume (variety mean: 0.82 vs. 0.70 cm³) and root dry weight (0.18 vs. 0.13 g), though these differences were not statistically significant (variety main effect: F (1,15) ≤ 2.36, p>0.05). The sole trait showing a significant variety effect was RCI (F (1,15) = 5.41, p<0.05), with Trisakti recording a higher mean. These moisture-responsive morpho-anatomical plasticity patterns provide a phenotypic reference for future comparative studies of climate-adaptive upland rice germplasm.